2009
DOI: 10.1042/bj20090978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology, genetics and biochemistry of the repulsive guidance molecule family

Abstract: RGMs (repulsive guidance molecules) comprise a recently discovered family of GPI (glycosylphosphatidylinositol)-linked cell-membrane-associated proteins found in most vertebrate species. The three proteins, RGMa, RGMb and RGMc, products of distinct single-copy genes that arose early in vertebrate evolution, are ~ 40–50%identical to each other in primary amino acid sequence, and share similarities in predicted protein domains and overall structure, as inferred by ab initio molecular modelling; yet the respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 86 publications
(214 reference statements)
0
58
0
Order By: Relevance
“…RGMc have been implicated in BMP signaling (Corradini et al, 2009;Severyn et al, 2009). We have previously shown that the C. elegans RGM protein DRAG-1 is a positive modulator of Sma/Mab signaling (Tian et al, 2010).…”
Section: Research Article Development 140 (19)mentioning
confidence: 99%
“…RGMc have been implicated in BMP signaling (Corradini et al, 2009;Severyn et al, 2009). We have previously shown that the C. elegans RGM protein DRAG-1 is a positive modulator of Sma/Mab signaling (Tian et al, 2010).…”
Section: Research Article Development 140 (19)mentioning
confidence: 99%
“…In particular, a family of repulsive guidance molecules (RGMs) has recently been found to bind different BMPs with high affinity and act as BMP coreceptors in tissue culture experiments Babitt et al, 2005;Babitt et al, 2006). RGM family proteins are GPI (glycosylphosphatidylinositol)-linked membrane-associated proteins Severyn et al, 2009). Vertebrates have four RGMs: RGMa, RGMb (DRAGON), RGMc (hemojuvelin or HJV) and RGMd (Camus and Lambert, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1A). Each RGM displays tissuespecific expression, is subjected to distinct biosynthetic and processing steps, and has not only unique, but also shared biological functions [2]. RGMs bind the type 1 transmembrane protein Neogenin ( Figure 1A) and many of the reported biological effects of RGMs rely on Neogenin receptor functions, such as axon guidance or neuronal survival [3,4].…”
mentioning
confidence: 99%
“…This processing serves to release RGMs from the cell surface in certain situations as well as to diversify the effects of the RGM signaling pathway and to control signaling duration following ligand binding. Here, we highlight some of the most recent insights into RGM processing and signaling in the context of specific biological functions, and refer readers to other reviews for a detailed discussion of other signaling mechanisms and biological effects [2,8,10,34,35]. …”
mentioning
confidence: 99%